2018
DOI: 10.1155/2018/3175214
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Dendropanax morbiferus Leaves Effectively Alleviated Neuroinflammation and Behavioral Impediments in MPTP‐Induced Parkinson’s Mouse Model

Abstract: Parkinson's disease (PD) is a commonly reported age-related neurodegenerative disorder. Microglial-mediated neuroinflammation is one of the cardinal hallmarks of various neurodegenerative disorders, including PD progression. Inadequate therapeutic strategies and substantial adverse effects of well-established drug candidates demand new therapeutic leads to treat PD. Dendropanax morbifera (DM) is an endemic plant species of South Korea, and it has been used extensively as traditional medicine to treat numerous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 53 publications
1
36
0
Order By: Relevance
“…(Carvalho et al, 2013) Captopril has shown signi icant improvement in motor coordina- tion, as evidenced through the rotarod test. Similarly improved motor co-ordination preventing the rat or mice from falling from the rotarod has been recorded after the administration of Dendropanax morbiferus leaves (Park et al, 2018) Apium graveolens (Chonpathompikunlert et al, 2018) (MPTP model), Juniperus communis (Bais et al, 2015) (CPZ model), caffeine (Khadrawy et al, 2017) (rotenone model) and with many other chine herbal medicines. (Kum et al, 2011;Pan et al, 2011) However, in the present study, captopril has not shown signi icant improvement in spontaneous locomotor activity in the rotenone model.…”
Section: Oxidative Stress Indicatorsmentioning
confidence: 77%
“…(Carvalho et al, 2013) Captopril has shown signi icant improvement in motor coordina- tion, as evidenced through the rotarod test. Similarly improved motor co-ordination preventing the rat or mice from falling from the rotarod has been recorded after the administration of Dendropanax morbiferus leaves (Park et al, 2018) Apium graveolens (Chonpathompikunlert et al, 2018) (MPTP model), Juniperus communis (Bais et al, 2015) (CPZ model), caffeine (Khadrawy et al, 2017) (rotenone model) and with many other chine herbal medicines. (Kum et al, 2011;Pan et al, 2011) However, in the present study, captopril has not shown signi icant improvement in spontaneous locomotor activity in the rotenone model.…”
Section: Oxidative Stress Indicatorsmentioning
confidence: 77%
“…Creatine [179,180] Cudraflavone B [181] Curcumin [89,117,[182][183][184] Cyanidin [185,186] D-512 [187] D-607 (bipyridyl-D2R/D3R agonist hybrid) [12,188,189] DA-2 (8D) [12,89] DA-3 [12] DA-4 [12] Dabigatran etexilate [190] Dabrafenib [191] (S)-3,4-DCPG [115] Deferasirox [24] Deferricoprogen [192] Delphinidin [160,185,193,194] Demethoxycurcumin [195] Dendropanax morbifera active compound [196] Desferrioxamine (Desferoxamine, Desferal, DFO) [112] (S)-N-(3-(3,6-Dibromo-9H -carbazol-9-yl)-2-fluoropropyl)-6-methoxypyridin-2-amine [197] 4,5-O-Dicaffeoyl-1-O-(malic acid methyl ester)-quinic acid derivatives (R1, R2, R3, R4, or R5 = caffeoyl) [198] Dihydromyricetin [199]…”
Section: -O-(3-chloropivaloyl)mentioning
confidence: 99%
“…Dendropanax morbiferus H. Lev, an endemic species in South Korea, has been used as an alternative traditional medicine for several diseases, such as headache, dysmenorrhea, infectious disorders, and skin disorders, for a long time (Jeong et al, 1995;Park et al, 2004;Lim et al, 2015). There are some reports that D. morbiferus shows anti-hyperuricemic, antiamnesic, anti-obesity, immunomodulatory, and antiinflammatory activities (Birhanu et al, 2018;Cho et al, 2018;Park et al, 2018a;Park et al, 2018b;Song et al, 2018;Sun et al, 2018b;Choo et al, 2019). The corresponding ingredients isolated from D. morbiferus leaves, such as 1-tetradecanol, dendropanoxide, rutin, gentisic acid, or oleifoliosides, have been reported to have diverse therapeutic potentials (Yu et al, 2012;Lee et al, 2013;Park et al, 2014;Park et al, 2017;Sun et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%